THE USE OF HIGH-STEM FORESTS AND COPPICE FORESTS DURING SOCIALISM IN ALBANIA AND THE FORMER YUGOSLAVIA - Laze, Kuenda (European Scientific Journal, ESJ, 2014)
This study investigatesthe use of high-stem forests, coppice forests, coniferous forests, broadleaved forests in socialist Albania and the former Yugoslavia. The inventory data of forests between 1953 and 1990 were used for both countries as well as forest data from remote sensing for three time steps of 1988, 2000 and 2007 for Albania. Method was descriptive statistics. Results showed that high-stem forests and coppice forests were used for industrial wood andfuel-wood. Broadleaved forests were harvested more than coniferous forests for industrial wood and fuel-wood. The share of fuelwood remained high for Albania and reduced for the former Yugoslavia during socialism. Forest transition of high-stem forests and coppice forests happened in socialist and post-socialist Albania but not in former Yugoslavia.